Utilisation of moringa oleifera (moringa) and pennisetum glandestinum (kikuyu) leaf meals by three commonly cultured fish species in South Africa : tilapia rendalli, oreochiromis, mossambicus and clarias gariepinus - Hlophe, Samkelisiwe Nosipho (University of Limpopo, 2015)
The ability to utilise dietary components differs between fish species. Digestive enzymes may be used to determine the efficiency of the digestive process. In this study, the activities of the digestive enzymes in Tilapia rendalli, Oreochromis mossambicus and Clarias gariepinus were explored. Protease, amylase, lipase and cellulase activities were measured in different parts of the digestive tract of the three fish species. The pH dynamics along the digestive tract were monitored. In all fish species, the presence of food led to a reduction in stomach pH. pH values of 1.54, 1.58 and 2.01 were recorded 12 hours after feeding in Oreochromis mossambicus, Tilapia rendalli and Clarias gariepinus respectively. Protease and amylase activities were significantly higher (P<0.05, ANOVA) in the tilapias than in Clarias gariepinus. The tilapias may be pre-adapted to produce more protease and amylase to digest plant material which is more difficult to digest compared to animal matter. In all species amylase activity was significantly higher in the proximal intestine than in the other parts of the digestive tract (P<0.05, ANOVA). The highest proteolytic activity was recorded in the distal intestines. This is because of the alkaline pH recorded in the proximal and distal intestines which favours for amylase and protease activity respectively. Lipase activities were not significantly different (P>0.05) in all species. Marginal cellulase activities were recorded in all species. It is inferred here that phylogeny and not diet may be the main factor influencing enzyme activities as all fish were fed a similar diet. Two locally available plant diets, kikuyu grass and moringa leaves, were tested as protein sources in the diet of a macrophagous fish, Tilapia rendalli (11.5±1 g). Nine diets (30% CP: 20 MJ/kg) were formulated by substituting fishmeal for kikuyu leaf meal (KLM) and moringa leaf meal (MLM). A control diet contained 10% fishmeal and no leaf meal. Fishmeal was replaced at 25, 50, 75 and 100% by KLM in diets: KLM 25, KLM 50, KLM 75 and KLM 100; then by MLM in diets MLM 25, MLM 50, MLM 75 and MLM 100. Each diet was fed to triplicate groups of fish for 60 days. The best growth (SGR, TGC) was in the control group. There was no significant (P>0.05) decrease in SGR and TGC when KLM replaced up to 50% fishmeal. There was a significant (P<0.05) decrease when MLM replaced >25% fishmeal. Kikuyu diets had no effect on villi height. A trend towards shorter villi was evident with increasing MLM. Digestive enzyme activities also decreased with increasing KLM and MLM vii levels in the diet. Hepatocyte degradation was higher in fish fed moringa-based diets. Anti-nutrients (polyphenols, tannins, saponins and phytate) in moringa may have contributed to the poor growth, irritation of the enterocytes and hepatotoxic effects. These results show that replacing up to 25% fishmeal with KLM is effective in reducing the costs without negatively affecting the growth performance or health of Tilapia rendalli. Adding MLM, even at the lowest level (25%) was expensive and resulted in compromised growth and health. The efficacy of KLM and MLM was also tested as alternative protein sources for Oreochromis mossambicus (12.5±1 g) a microphagous herbivore. The same diets used for Tilapia rendalli were fed to triplicate groups of twenty fish for 60 days. Linear regressions of feed intake, SGR, PER and protein ADC with increasing levels of leaf meal were significant (P<0.05). Superior growth performance, protein ADC and feed utilisation were also recorded in fish fed KLM-based diets than those fed MLM diets. When compared to Tilapia rendalli, Oreochromis mossambicus had superior growth performance and feed utilisation when fed the control diets and the lowest level of KLM. This was attributed to phylogeny. Protease, amylase and lipase decreased with increasing leaf meal levels and were higher in the intestine of fish fed KLMbased diets than those fed MLM-based diets. Fish fed MLM-based diets had higher number of goblet cells in the enterocytes, higher hepatocyte degradation and poor haematological parameters than those fed KLM diets. These adverse alterations were more pronounced in Oreochromis mossambicus compared to those observed in Tilapia rendalli feeding of the same diets. Cost benefit analysis also indicated that substitution fishmeal with KLM is a cheaper protein source in Oreochromis mossambicus diets. Kikuyu leaf meal may be used to replace up to 25% fishmeal without compromising the growth performance and health of Oreochromis mossambicus. Reduced growth and poor health was evident even at the lowest inclusion level of MLM. The effects of replacing fishmeal with KLM and MLM in the diets of a predatory omnivore, Clarias gariepinus were also investigated. The same KLM and MLMbased diets used in the previous experiments were used. Each diet was randomly assigned to triplicate groups of Clarias gariepinus (30.5±2 g) and fed to apparent satiation for 60 days. Significantly higher (P<0.05) growth performance, feed and viii protein utilisation was observed in Clarias gariepinus fed KLM diets compared to those fed MLM. Protein digestibility was higher in Clarias gariepinus fed the control diet than in both tilapias. However, in the treatment diets protein ADC was lower in Clarias gariepinus than in the tilapias. A decrease in the activity of digestive enzymes was also observed with increasing leaf meal level in the diet. This was attributed to the natural feeding habits and digestive adaptations of the different fish species. No histological alterations were found in liver of fish fed the control diet. Increased hepatocyte degradation was seen in fish fed higher levels of KLM and MLM in the diet. The enterocytes showed a significant increase in the number of goblet cells with increasing levels of MLM. Villi height decreased significantly (P<0.05) when MLM replaced >75 fishmeal. The damage to the hepatocytes and enterocytes as well as the poor health condition shown by haematological parameters was more pronounced in Clarias gariepinus than in the tilapias. This suggests that the predatory fish is not equipped to utilise high levels of leaf meals in its diet. The results of this study indicate that KLM can replace up to 25% fishmeal and that adding MLM resulted in reduced performance. Higher profit index and lower incidence cost was observed KLM diets than in MLM diets. Anti-nutrients in the leaf meals were the main factors leading to reduced feed intake and poor growth in fish fed the plant-based diet. Therefore, a subsequent study was undertaken to determine the efficacy of exogenous enzyme supplementation to reduce the negative effects of anti-nutrients and improve fish growth. A commercial multi-enzyme Natuzyme50® was supplemented at a rate of 0 (control), 0.25, 0.5, 0.75 and 1.00 g/kg DM feed in the best performing diet (KLM 25). These diets were tested in Oreochromis mossambicus. Natuzyme50® supplementation led to improved growth performance. Fish fed the diet containing 0.50 g/kg had the best growth performance and protein ADC and highest levels of digestive enzyme activities. At higher (>0.50 g/kg) enzyme supplementation levels, growth performance decreased. The improved growth performance with enzyme supplementation was attributed to the presence of enzymes such as cellulase and xylanase in the cocktail that are not naturally produced by fish. In addition, the activities of endogenous enzymes were enhanced. The optimal Natuzyme50® dietary level for optimal growth performance in Oreochromis mossambicus was 0.62 g/kg DM feed.
Thesis (Ph.D. (Agriculture)) --University of Limpopo, 2015
Keywords: Tillapia rendalli; Plant diets; Fish -- Food; Fish -- Feeding and feed